MARINE ALGAE DIVERSITY AT COASTAL AREA OF VERAVAL, GUJARAT (International Association of Biologicals and Computational Digest, 2022)
The Veraval coast situated at (20º54’30º N 76º21’20º E) the gulf of Kachchh, western coast of Gujarat, India. This site has a rich diversity of marine algae, corals and gastropods at intertidal region. The main aim of present study focused on occurrence and diversity of marine algae at coastal site. The study carried out in month of December- 2019. Algae collection was done during low tide situation, at this condition algae were collected with their holdfast/rhizoid. Total 33 species of algae were collected from three different phylum. Among these maximum 18 species were recorded from red algae, 8 species were recorded from green algae and 7 species were recorded from brown algae.